Investigation of Gas Local Effective Viscosity in Nano-scale Channels. (2015) - Luo, Shuangshuang; Bao, Fubing; Qiu, Limin
Abstract: The non-equilibrium molecular dynamics method is used in this paper to simulate the nano-scale shear-driven gas flows. The velocity gradients and shear stress profiles across the channel are first sampled according to molecular positions and thermal velocities. The Newton viscosity law is then adopted to obtain the local effective viscosity. By using this method, the distribution of effective viscosity across the channel is achieved for the first time. The effective viscosity in the bulk region of the channel agrees very well with the experimental data at different gas density and wall velocity. However, the local effective viscosity decreases when the fluid approaches the wall, because of the interactions between wall and gas molecules. The wall influence depth is independent of the wall velocity in Couette flow. However, this depth decreases with the increase of gas density due to more inter-molecule collisions.